Water - Feldman, David Lewis , 1951- (Resources, 2012)
Water is our planet's most precious resource. It is required by every living thing, yet a huge proportion of the world's population struggles to access clean water daily. Agriculture, aquaculture, industry, and energy all depend on it - yet its provision and safety engender widespread conflict